A naphthalimide derived fluorescent sensor for solid-phase screening of cucurbit[7]uril–guest interactions. Issue 11 (5th January 2016) - Aryal, Gyan Hari; Battle, Cooper Hawkins; Grusenmeyer, Tod A.; Zhu, Mengyuan; Jayawickramarajah, Janarthanan
Abstract : A fluorescent sensor displaying a significant increase in emission upon binding CB[7] was developed and utilized in a surface-bound displacement assay for the rapid detection of CB[7] encapsulation of therapeutically relevant drug classes. Abstract : A naphthalimide based fluorescent sensor displaying a significant increase in emission upon binding CB[7] with notable pH stability was developed and utilized in a surface-bound displacement assay for the rapid detection of CB[7] encapsulation of therapeutically relevant drug classes. Previously unknown binders with moderate to strong affinities were discovered.